KECENDERUNGAN WACANA BERITA JURNALISME WARGA DI LIPUTAN6.COM:KASUS KORUPSI DANA BANSOS COVID-19 MENSOS JULIARI BATUBARA - Nurfadhilah Bahar; Rahmawati Latief (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
This research examines the tendency of citizen journalism news discourse through Liputan6.com website. The cornerstone of this study is the analysis of critical discourse with the Teun A. Van Dijk approach model. This research aims to see the tendency of citizen journalism news discourse entitled “Mensos Juliari Batubara Tersangka Korupsi Bansos COVID-19, Warganet Tagih Janji Hukum Mati ke KPK" dated December 20, 2020 by describing the structure of the text and social context of the discourse. The research method used is to use a descriptive qualitative approach with research data in the form of discourse in citizen6 website which is a subkanal of Liputan6.com. The results found that the news contained three-dimensional text and analysis of its social context according to Teun A. van Dijk. The dimensions of the macro structure show that the topic of news discusses the punishments that are deserved by the corruptors of Bansos funds in this case by former Social Minister Juliari Batubara. The superstructure dimension shows news being rejuvenated in the full news text from start to finish to the one included in the situation section. The dimensions of microstructure represent semantic, stylistic and rhetorical aspects. While the social context that can be observed in the news implies that the news writer focused on asking for consistency of the KPK chairman to the statement of death penalty discourse for perpetrators of corruption of COVID-19 Bansos funds.